2004
DOI: 10.1128/jb.186.4.1021-1028.2004
|View full text |Cite
|
Sign up to set email alerts
|

OppA, the Substrate-Binding Subunit of the Oligopeptide Permease, Is the Major Ecto-ATPase ofMycoplasma hominis

Abstract: Most ATPases, involved in energy-driven processes, act in the cytoplasm. However, external membranebound ATPases have also been described in parasites and eukaryotic cells. In Mycoplasma hominis, a bacterium lacking a cell wall, the surface-exposed substrate-binding protein OppA of an oligopeptide permease (Opp) contains an ATP binding P-loop structure in the C-terminal region. With ATP affinity chromatography and tryptic digestion in the presence or absence of ATP, the functionality of the Mg 2؉ -dependent AT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 42 publications
4
34
0
Order By: Relevance
“…An additional variable is represented by the levels of ectonucleotidases, which rapidly hydrolyze the released ATP (32,33), thereby limiting IL-1␤ secretion, as confirmed by the strong increase in ATP and IL-1␤ in culture fluids when monocytes stimulations are carried out in the presence of ecto-ATPase inhibitors. Ecto-nucleotidases are expressed not only by monocytes (38), but also by parasites and bacteria (39), possibly representing an escape mechanism evolved by pathogens to limit the inflammatory response. Even in the presence of ATPase inhibitors, the ATP measured in monocytes culture fluids is well below the threshold required to stimulate P2X 7 R. This discrepancy has been found also in other experimental systems [astrocytes (32) and renal glomeruli (33)], where the ATP levels measured in extracellular media significantly underestimate the amount of ATP actually released at the cell surface, because of the fast diffusion and the rapid hydrolysis of the cell-derived ATP (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…An additional variable is represented by the levels of ectonucleotidases, which rapidly hydrolyze the released ATP (32,33), thereby limiting IL-1␤ secretion, as confirmed by the strong increase in ATP and IL-1␤ in culture fluids when monocytes stimulations are carried out in the presence of ecto-ATPase inhibitors. Ecto-nucleotidases are expressed not only by monocytes (38), but also by parasites and bacteria (39), possibly representing an escape mechanism evolved by pathogens to limit the inflammatory response. Even in the presence of ATPase inhibitors, the ATP measured in monocytes culture fluids is well below the threshold required to stimulate P2X 7 R. This discrepancy has been found also in other experimental systems [astrocytes (32) and renal glomeruli (33)], where the ATP levels measured in extracellular media significantly underestimate the amount of ATP actually released at the cell surface, because of the fast diffusion and the rapid hydrolysis of the cell-derived ATP (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…Mycoplasma hominis, an extracellular organism that colonizes the human urogenital tract, also possess an ecto-ATPase, although this enzyme is not a member of the NTPDase family (74). Surprisingly, a recent study demonstrated that this enzyme was able to induce apoptosis, and although the mechanism by which this occurred was not elucidated, it was postulated that it may be due to the generation of ADP and/or other breakdown products of ATP, again suggesting that ATP-utilizing enzymes of pathogens may influence purinergic signaling (73).…”
Section: Interference With P2 Receptor Signaling By Bacteriamentioning
confidence: 99%
“…Pyruvate dehydrogenase subunit E2 normally functions as part of a large structure that could be insoluble in nonionic detergents; however, none of the other subunits of pyruvate dehydrogenase was identified, suggesting a possible alternative or additional role for this protein, which also functions as a surface adhesin in other mycoplasmas (41). OppF is normally a peripheral membrane component of the oligopeptide ABC transporter (42), including in mycoplasmas (43). The substrate-binding protein component of this transporter, OppA, doubles as an adhesin in Mycoplasma hominis (44,45), raising the possibility that M. penetrans OppF anchors the material underlying the AO to OppA, acting as an adhesin.…”
Section: Discussionmentioning
confidence: 99%